Correlations between Ratings of Pain, Disability and Impairment in Chronic Whiplash-Associated Disorder. (1st December 1997) - Vernon, Howard
Abstract : OBJECTIVE: To investigate the level of correlation among pain, disability and physical impairment scores in chronic whiplash-associated disorder patients. SUBJECTS: Adults with chronic whiplash-associated disorder referred for secondary independent assessment. METHODS: Forty-four subjects (16 males, 28 females) were included in the sample. Self-rated pain was measured on a five-point verbal rating scale. Self-rated disability was measured using the Neck Disability Index (NDI) and the Disability Rating Index (DRI). Physical impairment was measured as active cervical ranges of motion obtained with a cap goniometer. Descriptive statistics were reported and Pearson product moment correlations were obtained with the P value at 0.01. RESULTS: Mean ± SD age of the subjects was 36.4±8.7 years. Mean duration of complaint was 15.2±12.3 months. Mean pain score out of 5 was 2.5±1.2. Mean NDI and DRI scores were 23.2±9.3 out of 50 and 21.6±9.1 out of 48, respectively. These scores correlated very highly (r=0.89, P=0.0001). The average reduction of ranges of motion compared with published norms was approximately 25%. The correlations among ranges of motion, NDI, DRI and pain scores ranged from -0.32 to -0.66 (P<0.05 to P=0.0001). Age and duration of complaint correlated poorly with ranges of motion. CONCLUSIONS: The self-ratings of pain and disability obtained from these chronic whiplash-associated disorder sufferers appear to be consistent with, and correlate reasonably well with, levels of physical impairment. Physical impairment ratings do not appear to correlate well with duration, which suggests that factors related to pain and physical impairment may play an important role in the development of chronicity in whiplash-associated disorder.